SAINS DALAM ALQURAN - Faisal, Muhammad (Prodi Ilmu Al-Qur'an dan Tafsir, 2021)
The interpretation of the Qur'an with the approach of bil'ilmi interpretation is one of the interpretation patterns in today's contemporary. This is more because of the development of technology and science that in contemporary times is felt very strongly. but. In fact, the development of this bil'ilmi interpretation approach has begun to appear in classical times, where one of the figures who played an important role in his birth was Imam Al-Ghazali. The presence of this interpretation of bil 'ilmi approach does not necessarily go according to the expected there are also pros and cons. Regardless of the support or rejection of this interpretation of bil 'ilmi, of course information about the existence of science has been explained in some letters in the Qur'an. one example is the process of human creation. In some verses God clearly explains how man's creation from the beginning until the formation of man was perfect. The phenomenon of human formation has been described in the Koran as about 1400 years ago, and its evidence in modern times today by using sophisticated tools such USG (Ultrasonografi ) tools both in the form of 2,3,4 dimensions used to see the development of fetuses in the womb. Qur'an is a book that provides a source of inspiration about science, where people in this case are instructed to continue to think in digging the content in the Qur'an so that human thinking continues to develop. And most importantly the signs of science in the Qur'an to make people more believe in Allah almighty through the signs of his power in the context of knowledge.